2019
DOI: 10.1101/lm.048579.118
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine, nicotine, and their conditioned contexts enhance consolidation of object memory in rats

Abstract: To test the hypothesis that drugs of abuse and their conditioned stimuli (CSs) enhance memory consolidation, the effects of post-training exposure to cocaine and nicotine were compared to the effects of post-training exposure to contextual stimuli that were paired with the effects of these drugs. Using the object recognition (OR) task, it was first demonstrated that both 10 and 20 mg/kg cocaine, and 0.2 and 0.4 mg/kg nicotine, enhanced recognition memory when administered immediately after, but not 6 h after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 93 publications
(105 reference statements)
2
27
0
Order By: Relevance
“…Contextual conditioning was conducted in six semitransparent Plexiglas compartments (30 × 40 × 26 cm) as described by Wolter et al 3,7 Locomotion was measured by automatic video tracking (EthoVision v3, Noldus, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Contextual conditioning was conducted in six semitransparent Plexiglas compartments (30 × 40 × 26 cm) as described by Wolter et al 3,7 Locomotion was measured by automatic video tracking (EthoVision v3, Noldus, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…One aspect of direct drug reinforcement is the enhancement of consolidation of memories for stimuli and behaviors linked to drug intake 2 . In fact, experimental posttraining administration of drugs of abuse such as alcohol, opioids, cocaine, nicotine, and amphetamine can improve the performance of various learning tasks 3–7 . Interestingly, it is possible that the persistence of behaviors aimed at avoiding the highly aversive affective state of drug withdrawal (hyperkatifeia) 8 also involves an action on memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that objects or situations that are associated in the addict's memory with the object of his or her addiction will arouse the desires and cravings that originally accompanied the addiction, even years after the addict was presumed to have overcome the addiction (Conklin, 2006;Siegel, 1999). A former drug addict, for example, may begin to experience such cravings when seeing drug paraphernalia or watching a movie with scenes of people using drugs (University of Guelph, 2019;Wolter, Huff, Speigel, Winters, & Leri, 2019). In a similar way, people who have recovered from an addiction to social media (or some other form of internet addiction) may again experience a craving to engage with social media when they see others using a computer or smartphone or when they themselves use a computer or smartphone for some purpose unrelated to social media (Ko et al, 2013).…”
mentioning
confidence: 99%